Proposed competency framework for Malaysian Technical And Vocational Education And Training (TVET) teachers - Hamisu, Mohammed Adamu; Mohd Salleh, Kahirol; Lai, Chee Sern; Abubakar, Auwal (2017)
Many issues have been taking place in the academia including Malaysian TVET institutions, which give rise to the need for continuous learning and updating competencies of TVET teachers across all ages. The purpose of this paper is to propose the competency Framework of TVET teachers by investigating the competency needs in Malaysian institutions. Primary data were collected using questionnaires to reveal the perceptions of thirty TVET teachers based on their competency needs. The result shows that the TVET teachers perceived all the twenty five competencies as important and the findings also shows the accepted Cronbach’s Alpha. The paper concerns on only TVET teachers perceptions on competency needs in their institutions. The paper provides an important pilot analysis on proposed competency framework of TVET teachers to enable further analysis in the area to be carried out.